Expanding the quality concept to satisfy consumer demand - Batt, Peter (Agricultural and Food Marketing Association for Asia and the Pacific-AFMA, 2007)
Personal disposable income has a significant impact on the food consumers purchase, where they buy it and where they consume it. With increasing income there is a corresponding increase in the desire for more convenience, a greater variety of food and higher quality food. Quality can be conceptualized at five levels. At its most basic level, quality captures the consumers' requirement for food that is nutritious, safe to eat and true to description. The intrinsic quality considers the physical attributes of the product. Extrinsic quality considers the value that the brand, the package, the place of purchase and the price add to the product. As attributes such as taste, texture and flavour can only be ascertained after purchase, such are described as the experiential quality attributes. The credence attributes are those that consider how the food was produced. With rising income, consumers want to know where the food was produced, what it contains and how it was produced. Concern for the environment, sustainable production and worker welfare and animal welfare are expected to become more influential in consumer decisions to purchase as they become more affluent.